A Suitable Structure to Control the System of Quad-rotor Miniature Aerial Vehicles - Van-Dai Bui; Trong-Thang Nguyen; Ngoc-Hoan Than; Duc-Minh Nguyen (Institute of Advanced Engineering and Science, 2018)
Miniature Aerial Vehicles with four rotors is called Quad-rotor MAV, popularly used in aspects of life such military, civilian products, processes and remote sensor, etc. In this paper, the authors present the suitable structure of control system for the Quad-rotor MAV. The first, the Six Degrees of Freedom (6 DOF) of the Quad-rotor MAV dynamic model is built. After, the control structure with the single loop is built. But in the single-loop system, only four control signals of Quad-rotor MAV can be controlled, so the Quad-rotor MAV can be reached the height only and keep the stability. However, it is important to note that we have to well-known the orbit of the Quad-rotor MAV flight; the Quad-rotor MAV must fly point-to-point exactly, so the six coordinate variables must be controlled. So, the double loop control structure system is proposed to do that. Finally, the simulation results analysis and the experimental results of the real model are explored to prove the effectiveness of the proposed structure.